The potential of Terminalia chebula in alleviating mild cognitive impairment: a review - Gao, Huimin; Lu, Hanyu; Fang, Nengqiao; Su, Jinsong; Li, Rui; Wang, Wenjun; Zhang, Yi (Frontiers in Pharmacology, 2024)
Terminalia chebula Retz. (T. Chebula, ཨ་#་ར།) is highly utilized in ethnic medicine. Its medicinal value is gradually being recognized and shows great potential in the improvement of mild cognitive impairment (MCI) disorders. Tibetan medicine theory classifies this type of disease as one of the "Jie Xie Syndrome (བ'ེ ད་*ེ ད།)." The role of T. Chebula in such diseases has been increasingly studied. This work aimed to elucidate the research progress of T. Chebula in alleviating MCI. The review offers a critical update on the current understanding of the effect of T. Chebula on MCI and highlights new opportunities for exploring its therapeutic potential. This review discusses the role of T. Chebula in alleviating MCI and provides a comprehensive overview of the traditional medicinal uses, chemical composition, toxicology, and quality control aspects of T. Chebula. This review covers 171 chemical constituents and 11 active constituents targeting MCI, such as flavonoids, which can alleviate MCI, primarily through its antioxidative, anti-inflammatory, and neuroprotective properties. T. Chebula shows potential as a natural medicine for the treatment and prevention of MCI.As an important part of ethnomedicinal resources, this work offers valuable insights for future research on T. Chebula-containing ethnomedicines. Research on traditional drug treatments, optimized treatment standards, improved societal knowledge about MCI, and development of an early detection system is essential to the diagnosis and treatment of MCI. These efforts will provide better treatment resources for patients with MCI.